North America materials, Papers, 1817-1883, relating to North American Indian missions - United Church Board for World Ministries (1817)
These papers include letters, reports, accounts, and memoranda relating to the work of the American Board of Home Missions among the Abenaki, Cherokee, Chickasaw, Choctaw, Creek, Dakota, Ojibwa, Miami, Osage, Pawnee, Penobscot, and Stockbridge-Munsee peoples of Arkansas, New York, and Oregon. Originals in Houghton Library, Harvard University.